An Update on Coat Protein Complexes for Vesicle Formation in Plant Post-Golgi Trafficking - Law, Kai Ching; Chung, Ka Kit; Zhuang, Xiaohong (Frontiers in Plant Science, 2022)
Endomembrane trafficking is an evolutionarily conserved process for all eukaryotic organisms. It is a fundamental and essential process for the transportation of protein, lipid, or cellular metabolites. The aforementioned cellular components are sorted across multiple membrane-bounded organelles. In plant cells, the endomembrane mainly consists of the nuclear envelope, endoplasmic reticulum (ER), Golgi apparatus, trans-Golgi network or early endosome (TGN/EE), pre-vacuolar compartments or multivesicular bodies (PVCs/MVBs), and vacuole. Among them, Golgi apparatus and TGN represent two central sorting intermediates for cargo secretion and recycling from other compartments by anterograde or retrograde trafficking. Several protein sorting machineries have been identified to function in this process for cargo recognition and vesicle assembly. Exciting progress have been made in recent years to provide novel insights into the sorting complexes as well as the underlying sorting mechanisms in plants. Here we will highlight the recent findings for the adaptor protein complexes (AP), retromer and retriever complexes, as well as their functions in the related coated vesicle formation in post-Golgi trafficking.